Xdy-ydx=2dy

Simple and best practice solution for Xdy-ydx=2dy equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Xdy-ydx=2dy equation:


Simplifying
Xdy + -1ydx = 2dy

Reorder the terms:
-1dxy + dyX = 2dy

Solving
-1dxy + dyX = 2dy

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-2dy' to each side of the equation.
-1dxy + -2dy + dyX = 2dy + -2dy

Combine like terms: 2dy + -2dy = 0
-1dxy + -2dy + dyX = 0

Factor out the Greatest Common Factor (GCF), 'dy'.
dy(-1x + -2 + X) = 0

Subproblem 1

Set the factor 'dy' equal to zero and attempt to solve: Simplifying dy = 0 Solving dy = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-1x + -2 + X)' equal to zero and attempt to solve: Simplifying -1x + -2 + X = 0 Reorder the terms: -2 + X + -1x = 0 Solving -2 + X + -1x = 0 Move all terms containing d to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + -1x = 0 + 2 Reorder the terms: -2 + 2 + X + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + X + -1x = 0 + 2 X + -1x = 0 + 2 Combine like terms: 0 + 2 = 2 X + -1x = 2 Add '-1X' to each side of the equation. X + -1X + -1x = 2 + -1X Combine like terms: X + -1X = 0 0 + -1x = 2 + -1X -1x = 2 + -1X Add 'x' to each side of the equation. -1x + x = 2 + -1X + x Combine like terms: -1x + x = 0 0 = 2 + -1X + x Simplifying 0 = 2 + -1X + x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| X^2+12x=17 | | 4(x+4)-10=-16 | | 75+2=4(5+1) | | 56x-12x+4=86 | | -2n+20=-2(3n+8)-2n | | 6(n+4)=-10 | | W=260*2/3 | | 9x+x=3x | | 5x+4+16=1 | | 260=2l(2w•2/3) | | 6(n-5)=-33+6n | | 7+x=-3x | | (x-4)=3x+4 | | 5/10=b/2 | | 4a-135=a/4 | | -6+4(-5+4n)=11+n | | 2w-3w=8w | | 1/4y=7/8 | | 12x+18=11x-7 | | 17/18x73 | | 5x+6-11=4x+3 | | 4/3(3.14)(9)E3 | | -6x-4(-6x-3)=257 | | 260-2/3 | | 4x-1=120 | | 6x+4-2x=16 | | -4(5-w)-(4w-8)=-12 | | -4(5-6)-(4w-8)=-12 | | -8+4v=12 | | 4/3(3.14)(3)E3 | | 8(x-2)=4y | | 4x+20=7x-25 |

Equations solver categories